IMPROVEMENT OF TEACHER ABILITY KARTIKA XIX 2 BANDUNG HIGH SCHOOL IN MAKING LESSON PLAN (RPP) BASED ON INQUIRY PERMENDIKBUD NO. 22 IN 2016 - Aryanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The use of learning strategies is one of the factors that can develop potential and improve student’s learning outcomes. A learning activity will succeed if a teacher is able to apply the right approach, model, method, and learning media. Inquiry model is one of the learning models that can improve the ability to plan and carry out research to solve a problem. However, in fact, the results of preliminary studies show some teachers still have not used the inquiry model in their lesson plans, even though Basic Competence (KD) that can use the inquiry model is relatively there. This study aims to implement the academic supervision to improve the ability of high school teachers in making inquiry-based lesson plan that refers to Permendikbud No. 22, 2016. The research method used was school action research. The results showed that after academic supervision was carried out, the ability of teachers in making inquiry-based lesson plans that referred to Permendikbud Number 22 of 2016 had shown an increase, from cycle I to cycle II. Cycle II ended the formation with the minimum teacher score indicator 75.00 already above 85%, which was 100%.